Estate Agency Malaysia: Impacts of Digital Marketing - Ying, Tan Jia; Wan Yusoff, Wan Zahari (Research in Management of Technology and Business, 2020)
Digital marketing (DM) become an essential part of marketing mix in real estate agency (EA) industry nowadays. Since there are different outcomes from many real estate agencies, it is believed that the results of the studies might not be applicable to local estate agency firms. Thus, this paper aimed to identify the impacts of digital marketing towards the practice of registered estate agency (REA) firms in Malaysia. The authors carried out the data collection by interviewing seven active REAs who had at least ten-year experience in property industry. After analysed the data by using qualitative content analysis, the study found that REAs from headquarter offices more preferred digital marketing. In addition, the interview findings also revealed that the adoption of digital marketing affected the most on relationship between the agents and customers. For the further study, the researchers can focus on the insights from property buyer side regarding the acceptance towards the adoption of DM in property market, and also can study the impacts of COVID-19 on the DM practicing in EA industry.